Mongolia Financial Sector Assessment : Housing Finance - World Bank (World Bank, Washington, DC, 2017)
As the Mongolian mortgage market grows rapidly, and the Government of Mongolia (GoM) pursues an ambitious social housing agenda, there is an urgent need for a holistic sector approach. The following three key areas require attention from policymakers: first, there is a need to better balance housing supply and demand, which requires the authorities to focus on prudent mortgage lending standards and supervision, as well as on provision of housing infrastructure and zoned land. Second, it will be important to ensure effective implementation of ongoing and planned public housing finance programs, with a focus on preventing mortgage market distortions in pricing, emphasizing robust planning and rigorous transparency and governance. Third, authorities should aim for better balance in the composition of mortgage funding, with a focus on improvement in the legal and regulatory framework for capital markets, as well as Mongolian Mortgage Corporation (MIK) governance, products and operations. The Mongolian mortgage market is exhibiting strong growth, with portfolio outstanding increasing by 190 percent to Mongolian Tughrik (MNT) 656 billion (US$482 million) between 2009 and end-2011. This represents 8 percent of 2010 gross domestic product (GDP) and 12 percent of the 2011 banking loan book. The sector is highly concentrated, with top 4 lenders accounting for 89 percent of the market, as well as spatially in and around Ulaanbaatar. Housing prices have risen sharply in the last two years, particularly in 2011, when the increase for the predominantly mortgaged market segment was over 36 percent. While mortgage lending growth rates are consistent with the overall growth of household credit, real estate prices significantly outpaced Consumer Price Index (CPI) and GDP growth in 2011. Currently non-performing loans (NPL) are very low due to the unseasoned mortgage portfolio; however, high debt-to-income (DTI) ratio levels may exacerbate future loan age-related and cyclical delinquency increases. Due in part to extreme climatic constraints, shortage of zoned and serviced land, and infrastructure bottlenecks, housing supply is severely constrained. Large-scale, publicly-funded, subsidized housing initiatives, such as the '100,000 Apartments' Program, need to be carefully planned, so that they cause minimal distortion to the broader housing finance market.